MEDIA MASSA DALAM KAMPANYE GEMPUR ROKOK ILEGAL - Muhammad Afandy Andy (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2022)
Mass media has a considerable role in a campaign agenda. Their broad reach makes mass media an effective means to spread information. Against Illicit Cigarette Campaign made by Directorate General of Customs and Excise employed a range of mass media, from conventional to internet/digital-based mass media. The campaign was performed further by PR of the Customs Service Office in Indonesia. The study was categorized as an exploratory qualitative descriptive work. The data were collected through interviews and direct observation in the Customs Service Office of Parepare. This study was conducted in the Customs Service Office of Parepare whose working territory exhibits one of Indonesia's highest volumes of illicit cigarette distribution. The result concludes that the PR department employed almost all conventional mass media to support their campaign and use the internet also. And, small format mass media was found to be highly effective in supporting the campaign.